Extensive enactivism: why keep it all in? - Hutto, Daniel D.; Kirchhoff, Michael D.; Myin, Erik (Frontiers in Human Neuroscience, 2014)
Radical enactive and embodied approaches to cognitive science oppose the received view in the sciences of the mind in denying that cognition fundamentally involves contentful mental representation. This paper argues that the fate of representationalism in cognitive science matters significantly to how best to understand the extent of cognition. It seeks to establish that any move away from representationalism towards pure, empirical functionalism fails to provide a substantive ‘mark of the cognitive’ and is bereft of other adequate means for individuating cognitive activity. It also argues that giving proper attention to the way the folk use their psychological concepts requires questioning the legitimacy of commonsense functionalism. In place of extended functionalism – empirical or commonsensical – we promote the fortunes of extensive enactivism, clarifying in which ways it is distinct from notions of extended mind and distributed cognition.